2016
DOI: 10.1158/1541-7786.mcr-16-0099
|View full text |Cite
|
Sign up to set email alerts
|

Targeting RRM2 and Mutant BRAF Is a Novel Combinatorial Strategy for Melanoma

Abstract: The majority of melanoma patients harbor mutations in the BRAF oncogene, thus making it a clinically relevant target. However, response to mutant BRAF inhibitors (BRAFi) is relatively short-lived with progression free survival of only 6–7 months. Previously, we reported high expression of ribonucleotide reductase M2 (RRM2), which is rate limiting for de novo dNTP synthesis, as a poor prognostic factor in mutant BRAF melanoma patients. In this study, the notion that targeting de novo dNTP synthesis through knoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…In previous work, we identified that Ewing sarcoma cells are sensitive to iron chelators and other drugs that inhibit RNR [ 21 ]. Inhibition of RNR is known to deplete nucleosides and cause DNA replication stress [ 32 34 ]. To test whether Ewing sarcoma cells are sensitive to DNA replication stress caused by mechanisms other than inhibition of RNR, we treated Ewing sarcoma and control cell lines with aphidicolin, which is an inhibitor of DNA polymerase α and δ and a drug that is frequently used to synchronize cells in S-phase [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work, we identified that Ewing sarcoma cells are sensitive to iron chelators and other drugs that inhibit RNR [ 21 ]. Inhibition of RNR is known to deplete nucleosides and cause DNA replication stress [ 32 34 ]. To test whether Ewing sarcoma cells are sensitive to DNA replication stress caused by mechanisms other than inhibition of RNR, we treated Ewing sarcoma and control cell lines with aphidicolin, which is an inhibitor of DNA polymerase α and δ and a drug that is frequently used to synchronize cells in S-phase [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of RNR is known to cause cell cycle arrest and senescence in multiple types of cancer [ 32 34 ]. However, in Ewing sarcoma cells, in direct contrast to the other cell types we tested, inhibition of RNR causes cell cycle arrest and subsequent cell death with up-regulation of markers of apoptosis [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear accumulation of RRM2, which allows efficient DNA repair, is preceded by downregulation of cyclin F. As it has been shown by D'Angiolella et al the insertion of wild-type cyclin F into hTERT RPE-1 cells prevents transposition of RRM2 from the cytoplasm to the nucleus ( 5 ). It has also been shown that overexpression of RRM2 may affect the proliferation of melanoma cells, their response to treatment in vivo , and is associated with worse overall survival in melanoma patients bearing mutations in the BRAF oncogene ( 8 , 11 , 12 ). Based on these data, we hypothesized that low expression of cyclin F in melanoma patients can be related to a poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of RRM2 inhibited melanoma growth which suggests the involvement of RRM2 in melanoma progression. Silencing of RRM2 and treatment with mutant BRAF inhibitor PLX4720 simultaneously and synergistically inhibited melanoma growth ( 11 ). It is possible that the negative effect of RRM2 overexpression is limited to patients bearing BRAF V600E mutation, but we cannot confirm this using TCGA data due to an insufficient number of patients with the BRAF mutation in the cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data from HGSOC patients suggest that senescence occurs in vivo after therapy and is associated with a better outcome (46). Indeed, other publications have also indicated that senescence is a beneficial therapeutic response (47,48,(60)(61)(62)(63). The mechanism of senescence induction by the combination of ATM inhibition and fenofibrate remains to be explored.…”
Section: Discussionmentioning
confidence: 99%